Tracheal Intubation Using Nelaton Catheter: A Simple Device, an Airway Rescue Option - Sezari, Parisa (Turk J Anaesthesiol Reanim, 2020)
Although anticipated, difficult airway could turn into a catastrophe for health care providers, where planned strategies and equipment become useless. We report a challenging airway management process due to narrowed upper airway by the application of a Nelaton catheter as a rescue device.